Decline in unmet needs for cataract surgery among the ageing population in India: findings from LASI, wave-1 - Das, Sasmita; Sinha, Abhinav; Kanungo, Srikanta; Pati, Sanghamitra (Frontiers in Health Services, 2024)
Introduction: Cataract is the leading cause of blindness among older people which can be treated with corrective surgery. India has the oldest blindness control programme in world.We aimed to assess the prevalence of cataract surgery; we compared the determinants of undergoing cataract surgery and the unmet needs for cataract surgery among older adults in India.Methods: We employed 52380 individuals aged ≥50 years from Longitudinal Ageing Study in India, wave-1. The main outcome measures of our study were the cataract surgery and unmet need for cataract surgery. Multivariate analysis was executed to investigate the association between socio-demographic variables and outcomes; expressed as adjusted odds ratio with 95% confidence interval (CI).Results: The overall prevalence of cataract was 14.85%. The coverage of cataract surgery was 76.95%, while 23% had unmet needs of cataract surgery. Specifically, cataract surgery coverage was notably higher 78.30% (95% CI: 76.88-79.48) among participants aged 66-80 years, and the percentage of those who did not undergo cataract surgery was higher 24.62% (95% CI: 23.09-26.20) among participants aged 50-60 years. The most deprived group had a higher odds [AOR: 1.20(95%CI: 1.00-1.44)] (P<0.05) of having unmet need for cataract surgery.Conclusions: There is a considerable burden of age-related cataract in India, but the coverage of cataract surgery is high. Nonetheless, the unmet need for cataract surgery cannot be overlooked. The existing blindness control programme has contributed significantly to increasing the coverage of cataract surgery but still needs to be strengthened especially to reach the most deprived section of society.